THE IMPACT OF LESSONS ORGANIZED BASED ON INTERACTIVE METHODS ON THE KNOWLEDGE LEVEL OF UNIVERSITY STUDENTS - Khamidova Aziza Khayrullaevna (The Conference Hub, 2026)
This study investigates the impact of lessons organized using interactive methods on the knowledge level of university students within the context of higher education. Specifically, the research aims to determine the extent to which interactive, student-centered instructional approaches enhance academic achievement compared to traditional teaching methods. A quasi-experimental research design was employed, involving control and experimental groups, and data were collected through pre-test and post-test assessments. The findings reveal a statistically significant improvement in the knowledge levels of students exposed to interactive teaching methods. Furthermore, the results indicate that interactive learning environments foster deeper understanding, active engagement, and meaningful knowledge construction. These outcomes highlight the pedagogical value of integrating interactive methods into university-level instruction. Consequently, the study contributes empirical evidence supporting the effectiveness of interactive teaching strategies and offers practical implications for improving instructional quality in higher education.
Keywords: Interactive teaching, higher education, knowledge acquisition, student engagement, active learning, pedagogical methods.